Global perspectives on youth participation in agriculture: A bibliometric analysis and literature review - Pathma , P K S; Ramasubramanian , M; Krishnan, R; Senthil Kumar, M; Saravanakumar , V (Plant Science Today, 2025)
Youth engagement in agriculture plays a vital role in strengthening food systems, promoting rural progress and enhancing economic resilience. Nevertheless, various socio-economic, institutional and environmental challenges often hinder their active participation. This study utilizes a bibliometric approach and comprehensive literature review to identify global patterns, core factors affecting youth involvement and regional disparities across developed, developing and underdeveloped nations. Key findings suggest that restricted access to land, financial hurdles, limited institutional backing and negative perceptions about agriculture collectively contribute to declining interest among young individuals. Despite these barriers, emerging developments in agricultural technology, supportive policies and evolving agribusiness models present new possibilities for youth involvement. Rather than offering a one-size-fits-all solution, the study underlines the importance of context-sensitive approaches, such as inclusive policy design, capacity-building initiatives and localized agricultural innovations, to make the sector more appealing and accessible to the next generation. These insights aim to guide policymakers and stakeholders toward creating an enabling environment for youth-led agricultural transformation that is both sustainable and inclusive.